PENGARUH NIK DIGANTIKAN DENGAN NPWP TERHADAP KESADARAN WAJIB PAJAK - Wati, Winda Risna (Universitas Pembangunan Panca Budi, 2023)
Taxes are very important in the life of the state and must be carried out as a citizen. However, it has also become a general law that the obligations of citizens go hand in hand with the rights of citizens, meaning that every tax obligation that must be paid by citizens has an impact on achievements that are entitled to be received by citizens, although indirectly. The issue of taxpayer compliance is an important issue in all countries, both for developed and developing countries. Taxpayer compliance in paying taxes is an important factor for a country in development. However, to grow this compliance, taxpayers must first be aware that taxes are the largest source of state revenue, be aware that by paying taxes, taxpayers will participate in the development of a country, be aware that delaying tax payments can harm the state, and be aware of the existence of laws and regulations. -laws and tax provisions. Therefore, the Government is trying to replace NPWP with NIK with the aim that people are more aware of the importance of paying state taxes.